Effects of s-metolachlor on early life stages of marbled crayfish - Velisek, Josef; Stara, Alzbeta; Zuskova, Eliska; Kubec, Jan; Buric, Milos; Kouba, Antonin (Pesticide biochemistry and physiology, 2019)
The effects of s-metolachlor chronic exposure at concentrations of 1.1 μg/L (maximal real environmental concentration in the Czech Republic), 11 μg/L (environmental relevant concentration) and 110 μg/L on early life stages of marbled crayfish (Procambarus virginalis) was evaluated under laboratory conditions. All s-metolachlor exposures resulted in higher mortality, delay ontogenetic development with accompanied slower growth and excited behaviour (increase of total distance moved and walking speed). Significantly lower superoxide dismutase, catalase, glutathione S-transferase activity and reduced glutathione level was observed at two higher tested concentrations (11 and 110 μg/L) of s-metolachlor compared with the control. S-metolachlor in concentrations 110 μg/L showed alteration of the tubular system of hepatopancreas including focal disintegration of tubular epithelium and notable reduction in epithelial cells number, especially B-cells. In conclusion, potential risk associated with using of s-metolachlor in agriculture, due to effects on non-target aquatic organisms as documented on early life stages of marbled crayfish in this study, should be taken into account.
Keywords: Behavior, Animal; Herbicide; Toxicity test; Behaviour; Hepatopancreas; Herbicides; hepatopankreas; Ontogenetic development; Animals; ženské pohlaví; Procambarus virginalis; zvířata; Acetamides; herbicidy; severní raci; chování zvířat; acetamidy; Female; Antioxidant enzymes; Astacoidea